Simultaneous single-staged repair of anorectal malformation with tracheoesophageal fistula: Lessons learned - Ajay Narayan Gangopadhyay; Vaibhav Pandey (Wolters Kluwer Medknow Publications, 2017)
Introduction: Anorectal malformation (ARM) associated esophageal atresia (EA) with tracheoesophageal fistula (TEF) spawns special therapeutic propositions. The outcome of these patients banks on numerous factors. We performed this study with an aim to compare the outcome of single-staged simultaneous primary repair of both anomalies versus staged repair of these disorders. Materials and Methods: Retrospective review of cases with ARM and associated EA with TEF managed over a period of 5 years from July 2010 to June 2015 after ethical approval was undertaken. Patients were split into two groups based on whether they underwent staged repair (Group A) or single-staged simultaneous primary repair of ARM with TEF (Group B). Patient's records were analyzed for demography, weight, gestational age, associated anomaly, preoperative and postoperative sepsis screen results, early and late postoperative complications (at least up to 1 year of age). Patient's Kelly score for continence at the age of 3 years or more was compared. Observation: A total of 28 were included in the study. Among these, 17 were managed with staged procedure for ARM (Group A), whereas 11 underwent simultaneous single-stage repair of ARM with TEF (Group B). No difference in continence score was observed in outcome between the two groups (P = 0.96). Overall mortality in Group A at 1-year follow-up was 52.9% and in Group B was 43.4%. Conclusion: The simultaneous single-staged primary repairs result in better long-term outcome in our setup.